LITERACY, TRUST, AND RISK AFFECT SHARIA FINTECH FINANCING INTENTIONS ON UMKM ACTORS IN CENTRAL JAVA - Luluk Mu'afifah; Budi Sukardi (Universitas Islam Negeri Mataram, 2023)
This study aims to determine and analyse the effect of literacy, trust, and risk on financing intentions through Sharia Fintech on MSME players in Boyolali district, Central Java. The sampling technique used is purposive sampling with predetermined respondent criteria. This study uses a quantitative research method using a questionnaire through Google Forms as an online data collection material. The sample used in this study was 226 respondents of MSME players in Boyolali Regency. The test results with SEM-PLS prove that several factors have a positive and significant effect, namely the variables of trust and risk. On the other hand, there are variables that do not affect the literacy variable on Islamic fintech financing intentions.